THE RECONSTRUCTION OF SPATIAL DATA CREATION PROCESS AND ITS USABILITY IN INDONESIAN NATIONAL SPATIAL DATA INFRASTRUCTURE - Hari Ginardi, R. V. (GEOMATIKA, 2011)
With the usage of metadata as a reference for spatial data query, remote sensing images and other spatial datasets have been linked to their related semantic information. In the current catalogue systems, like those on satellite data provides, or clearinghouses, each remote sensing image is maintained as an independent entity. There is a very limited possibility to know the linkage of one dataset to another, even if one dataset has actually been derived from the other. It is an advantage for many purposes if the linkage among remote sensing image or other spatial data can be maintained or reconstructed. Within a collection of spatial datasets, processing steps are extracted from dataset metadata, and reconstructed using a directed acyclic graph (DAG) structure. By using an adjacency list to organize all adjacencies in the graph, a complete processing step for each dataset can be tracked in two directions: source datasets and destination (created) datasets. With the help of this reconstruction, an approach to evaluate the relatedness of a pair of dataset is introduced.The output of this research leads to an improvement of spatial data organization, where an adjacency list is used to maintain spatial dataset history link. This improvement can enhance the query of spatial data in a catalogue system, and enables dataset grouping or classification based on the relatedness of the dataset. For a decision support system, the list of the usage of each dataset can be applied for quality assessment or may serve as one parameter to evaluate the productivity of each dataset in a collection. Keywords : spatial data clearinghouse, metadata, relatedness, history reconstruction ABSTRAK Informasi tentang proses pembuatan suatu data spasial dapat direkam dalam metadata. Informasi tersebut kemudian direkonstruksi dengan memanfaatkan struktur data directed acyclic graph (DAG) , dan dengan menggunakan adjacency-list untuk mengimplementasikan seluruh relasi yang ada pada graph tersebut, seluruh langkah-langkah proses yang melibatkan suatu dataset baik sebagai sumber maupun target dapat direkonstruksi. Dengan bantuan rekonstruksi ini dimungkinkan untuk mengevaluasi keterkaitan (relatedness) satu dataset terhadap dataset lainnya. Riset ini memberikan perbaikan metoda dalam pengorganisasian spasial data, khususnya dalam mengelola runtutan proses pembuatan masing-masing dataset. Dengan menerapkan metoda ini, layanan query pada katalog system dapat makin dikembangkan dengan kemampuan mengevaluasi seluruh rangkaian proses pembuatan dataset, serta memungkinkan pengelompokan koleksi berdasarkan keterkaitannya dalam pembuatan dataset lainnya. Salah satu contoh pemanfaatan  lainnya adalah dalam pengawasan kualitas koleksi data spasial serta pengukuran produktifitas koleksi data spasial. Kata Kunci : spatial data clearinghouse, metadata, relatedness, rekonstruksi.